2015
DOI: 10.1590/1676-06032015018614
|View full text |Cite
|
Sign up to set email alerts
|

Foraging, oviposition sites and notes on the natural history of the harvestman Heteromitobates discolor (Opiliones, Gonyleptidae)

Abstract: The lack of data on the natural history often hampers phylogenetic studies on the evolution of behavior. Herein we provide quantitative field data on foraging and oviposition sites of a Neotropical harvestman belonging to a subfamily with a published phylogeny, Goniosomatinae. Heteromitobates discolor rests during the day on granitic boulders on rivers, laying eggs in sheltered and darker areas. The female guard the eggs and aggressively respond to approaching conspecific females. In the absence of the female,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We also found that females were more likely to return to their batches when they were displaced later in the day. This could be because they are nocturnal animals that move in and out of their shelter mainly later in the afternoon when it gets darker (Silva & Willemart, 2015). Unguarded eggs are also probably more vulnerable at night, as previously described in another Neotropical species (Chelini & Machado, 2012), and individuals displaced later in the day could have higher motivation to return (Goniosomatinae females do not leave their eggs/first instar immature unguarded to forage; Gnaspini, 1995).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…We also found that females were more likely to return to their batches when they were displaced later in the day. This could be because they are nocturnal animals that move in and out of their shelter mainly later in the afternoon when it gets darker (Silva & Willemart, 2015). Unguarded eggs are also probably more vulnerable at night, as previously described in another Neotropical species (Chelini & Machado, 2012), and individuals displaced later in the day could have higher motivation to return (Goniosomatinae females do not leave their eggs/first instar immature unguarded to forage; Gnaspini, 1995).…”
Section: Discussionmentioning
confidence: 92%
“…We studied H. discolor females in a Neotropical forest, at the Parque Estadual da Serra do Mar, in the city of Ubatuba, state of São Paulo. Females of use granitic natural shelters by rivers as oviposition sites (Silva & Willemart, 2015), and we collected the data by four rivers that cross the highway Rio-Santos (SP-101): Corisco River (Casa da Farinha), River Cachoeira da Bacia, River Marimbondo (Cachoeira da Renata) and River Camburi (see Silva & Willemart, 2015).…”
Section: Study Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Heteromitobates discolor usually is nocturnal, spending the day hidden in rocky crevices near rocky streams. At night, individuals forage on rocks and in low vegetation; they stand upright with their bodies raised and leg pair number two extended to detect any possible prey (Silva and Willemart 2015).…”
mentioning
confidence: 99%